Multilevel Analysis: Factors Related with Quality Service of Elderly Community Health Post in Sukoharjo Central Java - Deviana Tristian; Bhisma Murti; Argyo Demartoto (Journal of Epidemiology and Public Health, 2024)
Background: The quality of health services is the difference between patient expectations and their perceptions of the services they receive, thus the quality of health services shows the success of a health service. This study aims to analyze the factors that influence the quality of at the elderly community health post.Subjects and Method: This research was a cross-sectional study conducted at 25 at the elderly community health post in Sukoharjo Regency, Central Java in November 2023. The sample consisted of 200 elderly people using random sampling. The dependent variable is the quality of health services at the elderly community health post, while the independent variables are gender, age, number of visits, level of education, and income. Data collection was carried out using a questionnaire. Data were analyzed using multilevel linear regression analysis.Results: The results of multilevel analysis show that the assessment of the quality of health services decreases in elderly women (b= -0.82; CI95%= -1.65 to -0.01; p= 0.049), aged ≥66 years (b= -1.22, CI95%= -2.01 to -0.44; p=0.002), number of visits 6 times (b= -3.03; CI95%= -3.89 to -2.61; p <0.001), education ≥0.699, and income (b= -2.09; CI95%= -3.20 to 0.97; p<0.001). Posyandu has a contextual effect on assessing the quality of health services with ICC = 52.76%).Conclusion: The assessment of the quality of the elderly community health post service decreased in the elderly type, age ≥66 years, number of visits 6 times, education ≥high school, and income ≥Rp 2,000,000. at the elderly community health post shows quite large contextual effects on assessing the quality of health services. Keywords: Quality of health services, multilevel analysis, elderly